Review of the Fund's Transparency Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This review analyzes trends in publication of IMF documents and experience with various aspects of the transparency policy since July 2003, based on: Fund-wide data on publication; records of changes made to published staff reports; a survey of mission chiefs; and ten country case studies involving interviews with staff and Executive Directors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country Authorities; PP; Publication Lag; Publication Rate; Staff Report; China, People's Republic of